Protocolo de consulta de enfermagem na doença de Parkinson: um enfoque no autocuidado apoiado. - Alcimar Marcelo do Couto (2022)
INTRODUCTION: Defined as a movement disorder, Parkinson's disease, a chronic, neurological, degenerative and progressive condition, has become a challenge for health systems, with numerous repercussions for the individual, family and society. OBJECTIVE: To develop and validate a protocol for nursing consultations for people with Parkinson's disease, based on the conceptual model of supported self-care. METHODS: This is a mixed methods study carried out in two phases. The first phase consisted of two stages: an integrative review of the literature in the Lilacs, Medline, CINAHL, Scopus, Cochrane, Embase and WOS databases and the documentary study, cross-sectional correlational analysis, carried out in a reference outpatient clinic in Belo Horizonte/MG , with 230 elderly people with a clinically confirmed diagnosis of Parkinson's disease. The medical records of the patients were evaluated focusing on the instruments: Clinical Functional Vulnerability Index - 20 and Care Plan of the multidimensional evaluation of the elderly. Data from this second stage were analyzed descriptively and by association of variables, verified using the chi-square, Fisher's exact and Mann Whitney tests. The second phase consisted of a methodological study in two stages: construction and content validation of the nursing consultation protocol for the self-care of people with Parkinson's, using non-probabilistic sampling consisting of twelve specialists. The protocol content validation instrument was designed to assess the relevance and clarity of the developed instrument. Two rounds of the Delphi method were performed. After evaluating the protocol instruments, the Content Validation Index was calculated for each item and globally. The research complied with national ethical precepts and was approved by the Research Ethics Committee of the Federal University of Minas Gerais. RESULTS: The results of the first phase, from the integrative review, demonstrate an incipient scientific production on the evaluation of the effectiveness of nursing interventions related to the care of people with Parkinson's in the national context. And it presented experiences and models of care identified in international studies that can be adapted and tested for incorporation into clinical practice and organization of comprehensive care services for Parkinson's disease in Brazil. The documentary study pointed out that among people with Parkinson's there is a predominance of elderly people classified as frail. There was a correlation between frailty and the variables: gender; age; age range; schooling; motor manifestations (tremor; rigidity; postural instability; speech/speech and chewing/swallowing); non-motor manifestations (cognitive disorder; mood disorder/depression; hallucinations/delusions; apathy and urinary disorder) and clinical manifestations (motor staging by Hoehn and Yahr and diagnosis time). All these data subsidized the second phase of the study, which consisted of the development of the nursing consultation protocol for self-care support for people with Parkinson's, consisting of six sections, 29 topics and 14 subtopics. The protocol was evaluated by 12 specialists and in the first round of the Delphi method, only three items did not reach agreement ≥ 0.80 among the judges and were reviewed, along with another eighteen items that, despite reaching agreement, were adapted because they presented suggestions considered relevant by researchers. The Content Validation Index of the developed protocol was already high in the first round (0.94) and, after the refinements performed, it increased to 0.99. CONCLUSION: The integrative review pointed to the need to create programs to support self-management and promote self-care actions, incorporating technological advances adapted for people with Parkinson's. Regarding the characterization of the elderly with Parkinson's, a high simultaneity of frailty conditions and Parkinson's disease was observed. At the end of the validation stage, the protocol was considered valid by the experts in terms of content. The clinical validation of the protocol still needs to be developed, seeking to identify barriers and adjustments in the profile of people with Parkinson's who really benefit from the proposed supported self-care methodology. The developed protocol allows the nurse to act using the principles of Systematization of Nursing Care, with greater autonomy and professional recognition.